Optimalisasi Pelaksanaan Regulasi Dalam Rangka Mengatasi Kredit UMKM Yang Bermasalah di Indonesia - Mujib Syaris (Universitas Semarang, 2020)
Non-performing loans affect national banking assets, which can be caused by external and internal factors both from the side of the banking and debtors. This study aims to find out and analyze how to optimize the implementation of regulations in order to overcome the problematic micro, small and medium enterprises (UMKM) loans in Indonesia. This study uses a normative juridical approach and is presented in a descriptive analytical form. The results show that efforts to overcome problem loans can be done before (preventive measures) and after the occurrence of problem loans (repressive measures), which are regulated in Bank Indonesia regulations. Regulations related to efforts to overcome problem loans must be carried out optimally in order to achieve benefits in the form of low numbers of problem loans in Indonesia.